Seismic hazard assessment and local site effect evaluation in Hanoi, Vietnam - Duong, Nguyen Anh; Nguyen, Pham Dinh; Tuan, Vu Minh; Duan, Bui Van; Linh, Nguyen Thuy (Vietnam Journal of Marine Science and Technology, 2017)
In this study, we have carried out the probabilistic seismic hazard analysis in Hanoi based on the latest seismotectonic data. The seismic hazard map shows peak ground acceleration values on rock corresponding to the 10% probability of exceedance in a 50-year time period (approximately return periods of 500 years). The calculated results reveal that the maximum ground acceleration can occur on rock in Hanoi is about 0.13 g corresponding to the shaking intensity level of VIII on the MSK-64 scale. The ground motion values calculated on rock vary according to the local site conditions. We have evaluated and corrected the local site effects on ground motion in Ha Dong district, Hanoi by using microtremor and borehole data. The Nakamura’s H/V spectral ratio method has been applied to establish a map of ground dominant periods in Ha Dong with a TS range of 0.6 - 1.2 seconds. The relatively high values of periods indicate that Ha Dong has soft soil and thick Quaternary sediments. The sediment thickness in Ha Dong is calculated to vary between 30 - 75 m based on ground dominant periods and shear wave velocity VS30 = 171 - 254 m/s. The results of local site effect on ground motion show that the 500-year return period peak ground acceleration in Ha Dong ranges from 0.13 g to 0.17 g. It is once again asserted that the seismic hazard in Hanoi is a matter of great concern, due not only to the relatively high ground acceleration, but also to the seismic characteristics of soil (low shear wave velocity, ground dominant period of approximately 1 second).